Intensive ultrafiltration strategy restores kidney transplant candidacy for patients with echocardiographic evidence of pulmonary hypertension. Issue 11 (4th September 2022) - Earasi, Kranthikiran; Mihaltses, John; Kennedy, Jamie L. W.; Rao, Swati; Holsten, Laura; Mazimba, Sula; Doyle, Alden; Mihalek, Andrew D.
Abstract: Introduction: Pulmonary hypertension (PH) is prevalent in those with end‐stage kidney disease (ESKD) and poses a barrier to kidney transplant due to its association with poor outcomes. Studies examining these adverse outcomes are limited and often utilize echocardiographic measurements of pulmonary artery systolic pressure (PASP) instead of the gold standard right heart catheterization (RHC). We hypothesized that in ESKD patients deemed ineligible for kidney transplant because of an echocardiographic diagnosis of PH the predominant cause of PH is hypervolemia and is potentially reversible. Methods: We conducted a prospective study of 16 patients with ESKD who were denied transplant candidacy. Prior echocardiograms and RHCs were reviewed for confirmation of PH. Patients were admitted for daily sessions of ultrafiltration for volume removal and repeat RHCs were performed following intervention. RHC parameters and body weight were compared before and after intervention. Statistical analysis was performed using PRISM GraphPad software. A p ‐value <.05 was considered statistically significant. Results: Following intervention, the mean pulmonary artery pressure (mPAP) and pulmonary arterial wedge pressure decreased from 45.0 ± 3.06 to 29.1 ± 7.77 mmHg ( p < .0001) and 22.2 ± 5.06 to 13.1 ± 7.25 mmHg ( p = .003), respectively. The pulmonary vascular resistance decreased from 4.73 ± 1.99 to 4.28 ± 2.07 WU ( p = .30). Eleven patients from the initial cohort underwent successful kidney transplantation post‐intervention with 100% survival at 1‐year. Conclusions: In ESKD patients, diagnoses of PH made by echocardiography may be largely due to hypervolemia and may be optimized using an intensive ultrafiltration strategy to restore transplant candidacy.